Advancing targeted therapy for colorectal cancer: harnessing ligand-directed enzyme prodrug therapy for highly specific interventions - Al-Jaber, Hend; Biswas, Kabir H.; Al-Mansoori, Layla (Frontiers in Oncology, 2025)
Colorectal cancer (CRC) is a significant global health burden, ranking as the third most frequently diagnosed cancer and a leading cause of cancer-related mortality. Current therapeutic modalities face challenges in advanced stages, including drug resistance, toxicity, and off-target effects. Ligand-Directed Enzyme Prodrug Therapy (LDEPT) has emerged as a promising strategy to address these limitations by delivering cytotoxic agents directly to tumor sites, minimizing damage to healthy tissues. LDEPT employs ligand-enzyme complexes that specifically target cancer cells, where the enzyme activates a prodrug into its cytotoxic form, enhancing precision, reducing adverse effects, and improving the therapeutic index compared to conventional chemotherapy. This review provides a detailed analysis of LDEPT’s core components while highlighting recent advancements in the field. Preclinical studies demonstrate promising outcomes, and initial clinical trials validate its potential. However, challenges remain, including optimizing ligand specificity, improving stability and delivery of ligand-enzyme complexes, and mitigating immune responses that may compromise effectiveness. Integrating LDEPT with immunotherapies or conventional chemotherapies could yield synergistic effects, paving the way for more comprehensive and personalized CRC treatment strategies. Continued research and clinical validation are essential to refine these approaches and transition LDEPT from experimental studies to routine clinical practice, with the potential to transform the treatment paradigm for advanced CRC.